Water quality and floating microplastics pollution along Southern to Northwestern Coast, Sri Lanka - M. G. Y. L. Mahagamage; P. Gajanayake; S. G. Gamage; D. Samarathunga; B. A. D. Peiris; M. M. K. I. Marasinghe; A. D. Igalavithana; H. D. L. Abeynayaka; A. Abeynayaka (Sri Lanka Journal of Aquatic Sciences, 2025)
Microplastics (MPs) are prevalent and dispersed in coastal ecosystems, heightening the risk of MPs consumption by marine wildlife, thereby leading to contamination of food webs. The present study investigated the abundance of MPs and respective water quality in coastal waters from Matara to Chilaw. MPs and water quality (pH, dissolved oxygen, electrical conductivity, turbidity, alkalinity, total dissolved solids, total suspended solids, total solids, and phosphates) were analysed in 12 sites in the study area in December 2021. MP analysis was done following the NOAA method and water quality was analysed according to the APHA standards. A total of 225 MP particles were found in all 12 sites covering Matara to Chilaw. The highest number of MP types was observed in the samples collected from Mattakkuliya (400 particles/m3). There were morphological differences among MPs and the highest to lowest morphological types were filament>film>fragment>pellets>foam, and the most dominant colour was blue. Based on FTIR analysis, polyethylene was identified as the most frequently detected (52%) polymer type of MPs in the analysed samples. Pearson correlation analysis indicated that there were no significant correlations among the water quality measures and MPs. However, further research is essential to determine the potential impacts of MPs on biotic and abiotic factors of the study locations.